PENGARUH PERTUMBUHAN EKONOMI, PENDAPATAN ASLI DAERAH (PAD), KOMPLEKSITAS DAERAH DAN BELANJA MODAL TERHADAP KELEMAHAN PENGENDALIAN INTERN PEMERINTAH DAERAH (Studi Empiris pada Pemerintah Daerah Provinsi di Indonesia periode 2011-2012) - Fitriatul Aini; Yuneita Anisma; Meilda Wiguna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to examine and obtain empirical evidence about the affecting factors that might influence internal control weakness. Those factors are economic growth, Region Own Source Revenue (PAD), complexity, and capital expenditure. Population of this study is the provincial level of goverment throughout Indonesia consisting of 33 provinces during 2011-2012 period. This research was carried out using secondary data from financial reports that are available in BPK’s website, Gross Domestic Regional Product (PDRB) report, realisation of regional goverment budget and data of number of municipalities (consists of districs and cities) throughout Indonesia and was analysed using multiple regression analysis with help of software SPSS version 20,0. The result shows that economic growth takes effect negatively-insignificant on internal control weakness at 0,090 > 0,05 level of significance. Region Own Source Revenue (PAD) takes its effect negatively-significant on internal control weakness at 0,001 < 0,05 level of significance. Complexity reacts positively-significant to internal control weakness at 0,000 < 0,05 level of significance. And level significance while capital expenditure doesn’t take any effect on internal control weakness at 0,527 > 0,05.Keywords: Internal Control Weakness, Economic Growth, PAD, Complexity, and Capital Expenditure